STUDI NILAI PRODUKTIVITAS PEKERJAAN PONDASI BORED PILE - Mubarak Mubarak; Alfa Taras Bulba; Mega Yunita (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
The success of a construction project is determined by a number of factors. One of the factors that play a direct role is a job productivity. Productivity can be expressed as the ability to complete a job within a certain time. The productivity is directly determined by the amount of the volume of work, the amount of labor/equipment, and implementation time. The larger the value of productivity, the greater the chance of a job can be completed by the target date. Therefor, this study aimed to assess the value of productivity on the bored pile foundation work. The study was conducted at the Project Tanjung Priok Access Road Construction Project (Phase I) Package 2, Section E-2, Cilincing - Jampea, North Jakarta. The study was initiated with field observations, by observing the completion of all stages of the process, andshall record the amount of labor / equipment and the turnaround time at each stage of thework. The volume of work is analyzed based on the design drawings. Productivity values for each phase of implementation of the work are: 1) the work of pre boring 46.71 m³/hr; 2) installation of casing 115.69 m/hr; 3) drilling by bucket 9.74 m³/hr; 4) ry by the bucket 81.70 m³/hr; 5) Cleaning by airlift 10.81 m³/hr; 6) test Koden 313.05 m/hr; 7) nstallation of rebar30.37 m/hr; 8) tremie pipe fitting 88.11 m/hr; and 9) casting concrete 89.56 m³/hr. Overall, the value of bored pile foundation work productivity is 3.14 m³/hr.